Analisis Kenaikan Pajak dalam Kerangka Keadilan, Kemaslahatan, dan Fiqh Sosial - Asmani, Jamal Ma'mur (Santri: Journal of Pesantren and Fiqh Sosial, 2025)
The Pati Regent Regulation Number 8 of 2025 provides legality for a 100% tax increase. However, the Regent increased the land and building tax (PBB-P2) to 250%. This increase aims to boost Regional Original Income, supporting infrastructure development programs and public services. This increase is intended to adjust the PBB-P2 rate after 14 years of no change. This increase in the PBB-P2 tax has caused pros and cons in society. In general, the community is burdened by this tax increase. This paper examines in depth whether this increase in PPB P2 tax is relevant. The research method employed is a robust descriptive-analytical approach, ensuring a comprehensive analysis. The theoretical framework used is justice, maslahah, and fiqh sosial, providing a solid foundation for the study. The analysis method employs critical discourse to examine the power that underpins the ideology of the dominant group, legitimizing its dominance. The results of this study indicate that the increase in PBB-P2 tax up to 250% is contrary to the values of justice, maslahah, and fiqh sosial, which lead to maqashidus shariah, namely protecting religion, soul, mind, property, and descendants. Justice demands that a leader prioritize honesty, solidarity, and compassion. The maslahah demands a leader who sides with the most vulnerable members of society. Meanwhile, fiqh sosial encourages the achievement of maqashidus sharia. The increase in the PBB-P2 tax suggests that a leader lacks honesty, compassion, and solidarity in acknowledging the suffering of their people.